Effect of N, P and Farmyard Manure on Noug (Guizotia abyssinica Cass.) Yield in Ebinat District - Wubie, Amare Aleminew; Damot, Getachew Alemayehu; HerreroVÃctor Flors (Journal of Agriculture and Environmental Sciences, 2019)
A field experiment was conducted under rain fed condition at Fakoy site in Debir Abajalie Peasant Administration of Ebinat District, Amhara Region on farmers’ field to study the response of integrated NP and FYM fertilizers application on yield and yield components of noug. The experiment was conducted using a factorial experiment laid out in a randomized complete block design with three replications. Four rates of FYM: 0, 2.5, 5 and 10 t ha-1 and four levels of NP; 0-0, 10.25-5.75, 20.5-11.5, and 41-23 kg N and P2O5 ha-1, respectively were used. The analysis of variance for growth and yield of noug revealed that there were highly significant (P<0.01) effects due to FYM and NP fertilizer levels. Generally, 10 ton ha-1 FYM with 20.5-11.5 kg ha-1 NP gave higher seed yield (1679 kg ha-1). Economic evaluation of noug against the treatments showed that net return (7305.00EB ha-1) was the highest for treatments that received 5 tonne FYM and 41-23 kg NP ha-1 in drill planting method. The present results emphasized the practical significance of integrated 5 tonne ha-1 FYM and 41-23 kg ha-1 NP fertilization were adequate for seed yield and oil content of noug in drill planting method.